Problems and Ways to Improve Results-Based Budgeting in Russia - A. I. Masterov (Финансы: теория и практика, 2019)
Based on the analysis of macroeconomic statistics, the article reveals the significance of programmatic approaches in budgeting concerning Russia’s state reflation. The purpose of the article is to identify problems impeding results-based budgeting in Russia and to find the ways to solve them. The methods of dynamic, system and factor analysis have been used. Foreign experience and best practices of program approaches in budgeting have been analyzed. It has been concluded that the following problems impede the effectiveness of introducing program approaches into Russia’s budgeting process: insufficient methodological elaboration of state programs; underdevelopment of planning institutions; low efficiency level of investment projects; poorly developed corporate sector of the economy. The authors have developed recommendations on increasing the effectiveness of the program approaches in Russia’s budgeting process: to create a specialized body responsible for developing the methodological support for results-based budgeting; to process current methodological support and to develop recommendations on improving the quality of economic planning; to introduce holding competitions for investment projects to get the right to implement them at the expense of the state budget. Further development of the results-based budgeting in Russia depends on the quality of the developed state programs and the effectiveness of individual investment projects. This requires improving the quality of planning and analytical calculations at the planning stage. The state should raise its attention to the quality of state programs as well as to the methodological support for planning investment projects implemented within the framework of the program approach.